Interactive Constructivist-Based Learning Media for Fifth Grade Indonesian Language in Elementary School - Kadek Andre Karisma Dewantara; Catur Satrio Adicondro; I Made Tegeh; I Komang Sudarma (Jurnal Media dan Teknologi Pendidikan, 2025)
The low level of Indonesian language literacy achievement among elementary school students, as indicated by international assessments, reflects that conventional teaching approaches have not yet fostered students’ critical and reflective thinking skills. This situation underscores the urgency of developing interactive and constructivist-based learning media that enable students to build knowledge through meaningful learning experiences. This study aims to analyze the validity and examine the effectiveness of an interactive constructivist-based learning medium in Indonesian language learning for fifth-grade students. The research employed the ADDIE development model encompassing analysis, design, development, implementation, and evaluation stages. The subjects involved a limited number of students in trial implementation and several experts who served as validators of content, design, and media. Data were collected through validation questionnaires and learning outcome tests, then analyzed descriptively and inferentially to determine the feasibility and effectiveness of the media. The findings reveal that the developed learning media are theoretically valid and empirically effective in enhancing students’ comprehension and reflective thinking in language learning. These results imply that constructivist-based interactive media can strengthen the quality of thematic learning practices in elementary education.